The diversity and conservation status of snakes in the eastern part of PT GAN, Riau Province - Nurdin, Muhammad; Setyawatiningsih, Sri Catur (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
PT Global Alam Nusantara (GAN) is one of ecosystem restoration concessions in Kampar Peninsula managed by Riau Ecosystem Restoration (RER). Unlike other companies under RER, information on the diversity of snake species in PT GAN is not yet available. Therefore, this study aims to determine the diversity and conservation status of snake species in PT GAN. There are 4 transects are placed systematically based on habitat conditions. Two transects are located near the river (transect 1 and transect 2), the other two transects are far from the river and are located around the peat dome (transect 3 and transect 4). Observations were made using the Visual Encounter Survey (VES) method on four observation transects. Data analysis used the Shannon-Wiener diversity index (H') and the Sorensen Index (IS). The snakes found were 16 individuals, belonging to three families and 11 species, namely: Ahaetulla prasina, Boiga jaspidae, Boiga cynodon, Boiga drapiezii, Coelognathus flavolineatus, Dendrelaphis caudolineatus, Dryocalamus subannulatus, Lycodon subcintus, Sibynophis melanochepalus, Tripodolaemus wagleri, and Calliophis bivirgatus. The diversity of snakes in PT GAN was moderate with a low Sorensen similarity index. All snake species found are unprotected, with low-risk IUCN status, and have not been included in the CITES appendix.